Assessment of Biofilm Formation and Resistance to Imipenem and Ciprofloxacin among Clinical Isolates of Acinetobacter baumannii in Tehran - Abdi-Ali, Ahya (Kowsar, 2014)
BACKGROUND: Biofilms are communities of bacteria attached to the surfaces in an extracellular polymeric matrix which are associated with many chronic infections in humans. Acinetobacter spp. are emerging as a major cause of nosocomial infections and Acinetobacter baumannii is the predominant species associated with this kind of infections. OBJECTIVES: In the present study, the potential of biofilm formation of clinical isolates, A. baumannii, was assessed by using crystal violet method. Furthermore, susceptibility pattern of these strains to ciprofloxacin and imipenem was determined. METHODS AND MATERIALS: Biofilm formation by 75 A. baumannii isolates was evaluated by using microtiter plate and tube methods and crystal violet staining. Tube method was carried out under static and shaking conditions. Then, the susceptibility of isolates to ciprofloxacin and imipenem was determined. RESULTS: Results showed that in tube method under shaking, 22% of clinical isolates were strong biofilm producers while 23% of them were not able to form biofilms. In this experiment, 18% and 42% of isolates were considered as moderate and weak biofilm-forming strains, respectively. In microtiter plate tests, 18% of strains were strong-biofilm producers and 25% of them were notable biofilm producers. In this assessment, 10% and 47% were considered as moderate and weak biofilm-forming isolates, respectively. The susceptibility tests, using microdilution method, confirmed that 92% of these isolates were resistant and 6.6% were susceptible to ciprofloxacin, although these results for imipenem were 68% and 24%, respectively. CONCLUSIONS: It can be concluded that most of A. baumannii isolates can form biofilm in microtiter plate and tube. The results also verified that most of these isolates were resistant to ciprofloxacin and imipenem.